Peramalan Harga Cabai Merah Besar Wilayah Jawa Timur Menggunakan Metode Extreme Learning Machine - Pindo Bagus Adiatmaja; Budi Darma Setiawan; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
In fulfilling economic needs in Indonesia the agricultural commodity sector has a very important role. Due to agricultural commodities are the livelihoods and basic consumption of the people in Indonesia. Daily people's needs cannot be separated from agricultural commodities, one of which is large red chili. This is due to the level of consumption of large red chili used for kitchen spices and the ingredients are quite high. Therefore large red chili which is included in agricultural commodities can be categorized as the primary food needs in people's lives. The prices of large red chili which are erratic and tend to rise can cause losses to the state and society. To overcome this problem, one solution is to forecast prices that can be used to predict the possibility of chili price increases quickly and accurately. This study aims to forecast the price of large red chili using the ELM method. Based on the results of the implementation and analysis that has been carried out using the data of large red chili prices from July 18, 2016 to December 28, 2018 the smallest error was obtained using Mean Absolute Error (MAPE) of 3 % using 2 feature, the number of neurons as many as 3 and the range of weight values ​​[-1,8, 1,8].